Djibouti : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
In this paper, the first section provides statistical information of main sectors, namely the real, fiscal, monetary, and external sectors. This information supplements the data contained in the staff report for the Article IV Consultation. The second section provides a summary of the tax system of Djibouti. Real sector, GDP by sector of origin, supply and use of resources, agricultural production, slaughter and exports of animals and skins, and transportation activity are discussed. Government revenues, expenditures, and tax exemptions are also reviewed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Summary Of The Tax System; Supplement The Data